A current conversion station for high voltage direct current transmission system - JIANG YING (2017)
The utility model provides a current conversion station for high voltage direct current transmission system (350). Current conversion station (350) are including first converter part (325) and joinable the second converter part (375) to second ploe (132) of joinable to first ploe (130). First converter part (325) and second converter part (375) can include the voltage source converter that is more than a series connection, and wherein at least one VSC of current conversion station includes at least one make perfect many level conversion of bridge module ization ware (120) to another VSC includes at least one half many level conversion of bridge module ization ware (122). 提供了种用于高压直流传输系统的换流站(350)。换流站(350)包括可连接到第极(130)的第转换器部分(325)和可连接到第二极(132)的第二转换器部分(375)。第转换器部分(325)和第二转换器部分(375)可以包括多于个串联连接的电压源转换器，其中换流站的至少个VSC包括至少个全桥模块化多电平转换器(120)，并且另VSC包括至少个半桥模块化多电平转换器(122)。